2017
DOI: 10.1080/21691401.2017.1388249
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial reparative functions of exosomes from mesenchymal stem cells are enhanced by hypoxia treatment of the cells via transferring microRNA-210 in an nSMase2-dependent way

Abstract: Hypoxia treatment enhances paracrine effect of mesenchymal stem cells (MSCs). The aim of this study was to investigate whether exosomes from hypoxia-treated MSCs (ExoH) are superior to those from normoxia-treated MSCs (ExoN) for myocardial repair. Mouse bone marrow-derived MSCs were cultured under hypoxia or normoxia for 24 h, and exosomes from conditioned media were intramyocardially injected into infarcted heart of C57BL/6 mouse. ExoH resulted in significantly higher survival, smaller scar size and better ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
184
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(189 citation statements)
references
References 37 publications
3
184
0
2
Order By: Relevance
“…Increasing evidence has indicated that the EV microRNA (miRNA) content as one of their most likely paracrine mechanism(s) of action. Several miRNAs have been associated with MSC-EV cardioprotective, pro-survival and angiogenic effects, including, for example, miR-21 [187]; miR-125b [188]; miR-320d [189]; miR-95-3p [190]; miR-210 [191]; miR-29 and miR-24 [180]. Additionally, EVs have been shown to biochemically restore ATP and NADH levels and redox state within the injured tissue [192].…”
Section: Contribution Of Exogenous Stem/progenitor Cell-evsmentioning
confidence: 99%
“…Increasing evidence has indicated that the EV microRNA (miRNA) content as one of their most likely paracrine mechanism(s) of action. Several miRNAs have been associated with MSC-EV cardioprotective, pro-survival and angiogenic effects, including, for example, miR-21 [187]; miR-125b [188]; miR-320d [189]; miR-95-3p [190]; miR-210 [191]; miR-29 and miR-24 [180]. Additionally, EVs have been shown to biochemically restore ATP and NADH levels and redox state within the injured tissue [192].…”
Section: Contribution Of Exogenous Stem/progenitor Cell-evsmentioning
confidence: 99%
“…Other studies also found significant enrichment of miRNA-125b-5p and miRNA-210 in exosomes from hypoxia-treated MSCs compared with those from normoxic MSCs. 30,31 In addition, Han et al 32 demonstrated that the levels of many cytokines, included vascular endothelial growth factor, epidermal growth factor and fibroblast growth factor were significantly higher in the exosomes derived from hypoxia-preconditioned adipose MSCs than in the exosomes derived from normoxic adipose MSCs. Many of these miRNAs and cytokines participate in the regulation of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al demonstrated that miR-210 enriched in BMSC-EVs drives endothelial proliferation and migration in vitro, and it improves cardiac angiogenesis and cardiac function after MI in mice by targeting Ephrin-A3 [17]. Zhu et al showed that BMSC hypoxic pretreatment increased the enrichment of angiogenesis-associated miRNAs in BMSC-EXs, which promoted angiogenesis more effectively and improved the therapeutic effects of MI treatment in mice [18].…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…revealed that EXs produced from hypoxia-preconditioned mouse BMSCs exhibited considerably improved learning and memory capabilities and reduced plaque deposition, neuroinflammation, and Aβ expression in an AD mouse model [11]. Zhu et al showed that hypoxia (0.5% O 2 ) stimulated exosomal mRNA-210 secretion through nSMase2 in mouse BMSCs to promote angiogenesis and improve cardiac function in a mouse model of MI [18].…”
Section: Hypoxia Culturementioning
confidence: 99%
See 1 more Smart Citation